PENGARUH PENATAAN PERMUKIMAN KUMUH UNTUK MENCAPAI LIVABLE SETTLEMENT DI KELURAHAN TAMBAKREJO KOTA SEMARANG - Leylita Hariaty Gultom; Sunarti Sunarti (Diponegoro University, 2017)
Limited ability of society both economically and managing space cause slum condition in Tambakrejo Urban Village. In the year 2015-2017 then done slum arrangement, but not yet reached livable settlement as environment condition which still not support based on condition and perception of society. Many found garbage that pollute the community environment. The purpose of this research is to know the effect of settlement arrangement to reach livable settlement in Tambakrejo Urban Village Semarang. The research method used in the form of quantitative approach, with descriptive analysis tool, likert scale and simple linear regression. Based on the research, founds that slum regulation in Tambakrejo Village has not reached livable, from 3 components that must be realized it only affect 2 aspects that is physical and social, while the economic aspect is still not influenced by the arrangement. Furthermore, people's assessment of 17 criteria of human settlement as convenience parameters, obtained 6 criteria influenced, among others, ease of access, satisfaction of infrastructure, infrastructure support activities, small home improvement costs, the role of socializing institutions, and guaranteed cooperation of government, private, and community.